Analisis Tingkat Pengetahuan Keselamatan dan Kesehatan Kerja (K3) Mengenai Lockout/Tagout (LOTO) terhadap Tindakan Tidak Aman (Unsafe Action) dalam Lockout/Tagout (LOTO) Pekerja Divisi Manufactur dan Divisi Enggenering pada PT. X Kabupaten Banyuwangi - Dea Artha Melati; Ekowati Retnaningtyas; Diniyah Kholidah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
PT.X is a business located in Banyuwangi district, East Java. PT.X is engaged in manufacturing which produces mineral water. PT.X Banyuwangi's work procedures have implemented K3 in its work processes. The Lockout/Tagout (LOTO) locking and marking system has been implemented, but unsafe behavior is still found by workers when carrying out work processes using the Lockout/Tagout (LOTO) system, such as not using PPE during machine repair/maintenance processes, and not installing tags. . . during repairs. This research aims to analyze the level of K3 knowledge about Lockout/Tagout regarding unsafe actions in implementing Lockout/Tagout among workers at PT. In general, this research is a type of quantitative research. The aim of using the crosstab method is to identify data patterns, such as the distribution of variable preferences based on the level of knowledge in carrying out actions. The results of the analysis were that 3 respondents in the good knowledge category carried out unsafe actions in the high category representing 37.5% of the total respondents, 5 respondents in the good knowledge category carried out unsafe actions in the low category representing 62.5% of the total respondents. total respondents. Then for the poor knowledge level category, there were 13 respondents who carried out unsafe actions in the high category, representing 56.5% of the total respondents, and 10 respondents who had poor knowledge levels carried out unsafe actions in the low category. representing 43.5% of the total respondents.